(untitled) (Journal of Fatima Jinnah Medical University, 2026)
Background: Methotrexate is a first-line disease-modifying drug for rheumatoid arthritis, and is conventionally administered as a single weekly oral dose. In clinical practice, the weekly dose is sometimes split over 24 hours to reduce gastrointestinal adverse effects, although supporting evidence remains limited. This study aimed to compare the safety and efficacy of a single-dose versus a split-dose of oral methotrexate. Methods: This open-label interventional study was conducted at the Department of Rheumatology, Sir Ganga Ram Hospital, Lahore, Pakistan, between January and August 2025. A total of 56 patients aged 15-70 years fulfilling the ACR/EULAR-2010 criteria were enrolled. Patients with serious comorbidities, a prior biologic or recent conventional DMARD therapy, or pregnancy and lactation were excluded. Patients were allocated using systematic allocation (odd-even method) to receive either a single weekly oral dose or a split 24-hour oral dose of methotrexate. Methotrexate was initiated at 10 mg/week and increased to 25 mg/week according to response and tolerability. All patients received folic acid supplementation and tapering of low-dose prednisolone. Patients were followed for 24 weeks. Disease activity was measured using the Clinical Disease Activity Index (CDAI). Remission (CDAI ≤ 2.8) was the primary effectiveness endpoint, and methotrexate-related adverse effects were the primary safety outcome. The chi-square test was used to analyze the data, and a p-value <0.05 was considered statistically significant. Results: Out of 56 patients, 47 completed the study (27.7% males and 72.3% females). Baseline disease activity was mild in 4.3%, moderate in 21.3%, and severe in 74.5%. Overall remission rates were 6.4% at week 12 and 34.0% at week 24. At week 24, remission was significantly higher in the split-dose group compared to the single-dose group (48.0% vs. 18.2%, p-value = 0.031). The single-dose group had a higher prevalence of nausea (36.4% vs. 12.0%, p-value = 0.049) and dyspepsia (31.8% vs. 8.0%, p-value = 0.038). The overall incidence of transaminitis was 25.5%, with no significant intergroup difference. Conclusion: Splitting the oral dose of methotrexate over 24 hours results in higher remission and improved gastrointestinal tolerability compared with a single weekly dose.